Implementasi Mindfulness-Based Learning dalam Pengembangan Regulasi Emosi dan Konsentrasi Belajar Siswa Sekolah Dasar - Khairani Arum Martaliana; Ade Bagus Primadoni, M.Pd.; Rachmat Imam Muslim, M.Pd. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the implementation of Mindfulness-Based Learning (MBL) in enhancing emotional regulation and learning concentration among elementary school students. The research is motivated by the declining attention span and emotional stability of students in the digital era, which affects the learning process. A descriptive qualitative approach was employed in this study. Data were collected through participatory observation, semi-structured interviews, and documentation conducted at SD Negeri Kranggan 02, Batang Regency, Indonesia. The research participants consisted of the principal, a fifth-grade teacher, and fifteen fifth-grade students selected through purposive sampling. The findings reveal that the implementation of Mindfulness-Based Learning, through activities such as mindful breathing, self-reflection, and brief moments of silence, helps students calm themselves, become aware of their emotions, and improve their learning concentration during classroom activities. Both teachers and students reported a calmer and more conducive classroom environment. These findings indicate that Mindfulness-Based Learning has the potential to be an effective instructional approach to support emotional regulation and learning concentration in elementary education, in line with the social-emotional development goals of the Merdeka Curriculum. Keywords: mindfulness-based learning, emotional regulation, learning concentration, elementary school